2022
DOI: 10.3102/01623737221111800
|View full text |Cite
|
Sign up to set email alerts
|

Round and Round They Go: The Relationship Between Changing Grades and Schools and Teacher Quality and Absence Rates

Abstract: Research on teacher churn has produced conflicting conclusions as to its impact on students and teachers. We bring clarity to this work by combining and expanding on analytical approaches used in earlier research to determine how and when different types of churn (i.e., grade, school) impact teacher effectiveness and attendance. Using data from the Los Angeles Unified School District, our results suggest differences based on analytical approach but ultimately show that changing schools and grades may be less o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A teacher may find conditions in one school to be unacceptable, but moving to a new workplace may alleviate the reasons for leaving the profession. Recent research has also looked at a phenomenon called teacher churn when teachers change grade levels, subject areas, or schools (Dhaliwal et al, 2023) to find a better "fit. " While this may be an apt partitioning of intention to leave for a future study, we focus on the primary workplace with which our study participants identified themselves.…”
Section: Emotional Resilience and Intention To Leavementioning
confidence: 99%
“…A teacher may find conditions in one school to be unacceptable, but moving to a new workplace may alleviate the reasons for leaving the profession. Recent research has also looked at a phenomenon called teacher churn when teachers change grade levels, subject areas, or schools (Dhaliwal et al, 2023) to find a better "fit. " While this may be an apt partitioning of intention to leave for a future study, we focus on the primary workplace with which our study participants identified themselves.…”
Section: Emotional Resilience and Intention To Leavementioning
confidence: 99%